Office-Based Deep Sedation for Pediatric Ophthalmologic Procedures Using a Sedation Service Model - Kirk Lalwani; Matthew Tomlinson; Jeffrey Koh; David Wheeler (Anesthesiology Research and Practice)
Aims. (1) To assess the efficacy and safety of pediatric office-based sedation for ophthalmologic procedures using a pediatric sedation service model. (2) To assess the reduction in hospital charges of this model of care delivery compared to the operating room (OR) setting for similar procedures. Background. Sedation is used to facilitate pediatric procedures and to immobilize patients for imaging and examination. We believe that the pediatric sedation service model can be used to facilitate office-based deep sedation for brief ophthalmologic procedures and examinations. Methods. After IRB approval, all children who underwent office-based ophthalmologic procedures at our institution between January 1, 2000 and July 31, 2008 were identified using the sedation service database and the electronic health record. A comparison of hospital charges between similar procedures in the operating room was performed. Results. A total of 855 procedures were reviewed. Procedure completion rate was 100% (C.I. 99.62–100). There were no serious complications or unanticipated admissions. Our analysis showed a significant reduction in hospital charges (average of $1287 per patient) as a result of absent OR and recovery unit charges. Conclusions. Pediatric ophthalmologic minor procedures can be performed using a sedation service model with significant reductions in hospital charges.